2022
DOI: 10.1097/mnm.0000000000001607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F-FDG PET/CT and 68Ga-FAPI-04 PET/CT in patients with non-small cell lung cancer

Abstract: In this study, we aimed to compare the diagnostic accuracy of 18 F−fluorodeoxyglucose ( 18 F-FDG) and Gallium-68 labeled fibroblast activator protein inhibitor ( 68 Ga-FAPI)-04 PET/CT in the tumor-node-metastasis (TNM) staging of patients with nonsmall cell lung cancer (NSCLC) and investigate whether adenocarcinoma (ADC) and squamous cell cancer (SCC) exhibit different uptake patterns on 68 Ga-FAPI-04 PET/CT. Materials and methodTwenty-nine patients with a histopathologically-confirmed diagnosis of NSCLC, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In addition, in volume-based evaluation; MTV, TLG and Hpeak values obtained from lymph nodes were found to be higher on FAPI imaging compared to FDG imaging. Although there is no study in the literature comparing lymph node metastases of only malignant mesothelioma patients, it has been reported that 68 Ga-FAPI-04 PET/CT is superior to 18 F-FDG PET/CT in detecting lymph node metastases in different tumor types and our findings support the literature [34–37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, in volume-based evaluation; MTV, TLG and Hpeak values obtained from lymph nodes were found to be higher on FAPI imaging compared to FDG imaging. Although there is no study in the literature comparing lymph node metastases of only malignant mesothelioma patients, it has been reported that 68 Ga-FAPI-04 PET/CT is superior to 18 F-FDG PET/CT in detecting lymph node metastases in different tumor types and our findings support the literature [34–37].…”
Section: Discussionsupporting
confidence: 90%
“…This finding may be due to the small number of patients with bone metastases. Despite this, five new bone metastases were demonstrated in two patients with 68 Ga-FAPI-04 PET/CT, and an upstage was observed in one patient [35,39–41].…”
Section: Discussionmentioning
confidence: 99%
“…9 In our previous studies with 68 Ga-FAPI-04 PET/CT in different tumor types, we reported its superiority over 18 F-FDG PET/CT in staging and detection of recurrence. 10,11 In this case, we demonstrated the superiority of 18 F-FDG PET/ CT in the detection of recurrence and metastases in adrenocortical carcinoma.…”
mentioning
confidence: 58%
“…In the evaluation of a wide spectrum of adrenal gland pathology with PET/CT performed with different radiopharmaceuticals, the most useful imaging was found to be with 18 F-FDG, although it was not found to be specific 9 . In our previous studies with 68 Ga-FAPI-04 PET/CT in different tumor types, we reported its superiority over 18 F-FDG PET/CT in staging and detection of recurrence 10,11 . In this case, we demonstrated the superiority of 18 F-FDG PET/CT in the detection of recurrence and metastases in adrenocortical carcinoma.…”
mentioning
confidence: 69%
“…This retrospective study included 63 patients with liver lesions who underwent 18 F-FDG PET/CT and 68 Ga-FAPI PET/CT in our clinic between May 2020 and May 2022. Some patients were from our previous prospective studies [12,13,14,15]. The inclusion criteria were as follows: both PET scans obtained at a maximum interval of 14 days, histopathologically confirmed primary diagnoses, age over 18 years; ECOG performance scores of 0-2, data that could be accessed retrospectively, and liver lesions evident on biopsy over at least 3-6 months of follow-up employing US, CT, MRI, PET/CT, and/or laboratory tests.…”
Section: Patient Selectionmentioning
confidence: 99%